STRENGTHENING SRADDHA THROUGH THE THREE BASIC FRAMEWORKS OF HINDUISM DURING THE COVID-19 PANDEMIC - Ida Ayu Gde Wulandari; I Gusti Ayu Jatiana Manik Wedanti (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
During the Covid-19 pandemic, there are many changes in society. These changes occur in changes in people's lives, education, and even religious aspects. In responding to this pandemic, the community also strengthened their faith to stay strong and positive in life, one of which was to understand the concept of the Three Basic Frameworks of Hinduism. In this concept, it is explained that humans in facing their life that exist are due will and on the based on “karma”. Nevertheless, humans continue to worship both individually and in groups (in the form of ceremonies) to address this problem from the noetic aspect; while the ceremonies should still observing the health protocol. This paper use the literature study method by collecting references or literature from various sources such as books and the internet related to this paper. This paper aims to describe the views on strengthening religious beliefs by Tri Kerangka Agama Hindu concept in this pandemic.